Uso de niveles de bicarbonato de sodio en la ración y su efecto en el desempeño productivo y calidad de huevo de codornices (Coturnix coturnix japonica) en Yurimaguas - Amesquita Jarama, Luis Alfredo (2021)
The research work took place in the city of Yurimaguas with the purpose of evaluating the use of sodium bicarbonate in the ration and its effect on the productive performance and quality of quail eggs (Coturnix coturnix japonica). Feed consumption, feed conversion, percentage of laying, egg weight, egg diameter and yolk index were evaluated, as well as economic merit, using 72 female quail in the laying phase, with a Completely Random Statistical Design, with four treatments and three repetitions and a degree of reliability (P <0.05). The treatments were T0 (Control treatment) 0 mg; T1: 100; T2: 200 and T3: 300 mg of sodium bicarbonate/kg of food. The results achieved for feed consumption were T0: 21.69g / bird; T1: 22.20 g/bird; T2: 22.95 g/bird; T3:23.29 g/bird, with significant statistical differences between treatments (P<0.05). Statistical differences (P<0.05) between treatments were found in the percentage of posture: T0: 85.83; T1: 91.66: T2: 96 and T3: 98.50%. Egg weight accumulated averages of T0: 9.74; T1: 9.91; T2: 10.54 and T3: 10.79 g. In the statistical analysis, these showed statistical differences between the means of the treatments. For the accumulated feed conversion, the values of T0: 2.23; T1: 2.25; T2: 2.18 and T3: 2.16, not finding significant statistical differences between treatments (P <0.05). For the diameter of the egg the treatments achieved T0: 3.05; T1: 3.05; T2: 3.09 and T3: 3.12 mm. Respectively. While for the yolk index, T3 achieves the best values with 48.25, followed by T2: 43.05, T1 with 39.98 and T0 with 32.57%. In the Economic Merit study, T3 showed the highest profitability with S/ 100.97.